2008
DOI: 10.1073/pnas.0703121105
|View full text |Cite
|
Sign up to set email alerts
|

Chemical transmission between dopaminergic neuron pairs

Abstract: Midbrain dopaminergic (DAergic) neurons play a major regulatory role in in goal-directed behavior and reinforcement learning. DAergic neuron activity, and therefore spatiotemporal properties of dopamine release, precisely encodes reward signals. Neuronal activity is shaped both by external afferences and local interactions (chemical and electrical transmissions). Numerous hints suggest the existence of chemical interactions between DAergic neurons, but direct evidence and characterization are still lacking. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…10) and could play a critical role in shaping the response of these neurons to inhibitory inputs. Indeed, 70% of the synaptic inputs received by SNc dopaminergic neurons are GABAergic (Tepper and Lee, 2007), while dopamine release between neighboring cells is also responsible for long hyperpolarizations (Vandecasteele et al, 2008). A recent study using dynamic clamp in SNc dopaminergic neurons demonstrated that their response to trains of simulated GABAergic inputs was influenced by I H properties (Tateno and Robinson, 2011).…”
Section: Functional Impact Of the Covariation On Physiological Activimentioning
confidence: 99%
“…10) and could play a critical role in shaping the response of these neurons to inhibitory inputs. Indeed, 70% of the synaptic inputs received by SNc dopaminergic neurons are GABAergic (Tepper and Lee, 2007), while dopamine release between neighboring cells is also responsible for long hyperpolarizations (Vandecasteele et al, 2008). A recent study using dynamic clamp in SNc dopaminergic neurons demonstrated that their response to trains of simulated GABAergic inputs was influenced by I H properties (Tateno and Robinson, 2011).…”
Section: Functional Impact Of the Covariation On Physiological Activimentioning
confidence: 99%
“…autoreceptor activation (6,7) and increases firing activity of SN pars reticulata ␥-aminobutyric acid-releasing neurons, a process that might activate feedback signals regulating DA neuron activity (8), thereby influencing axonal DA release.…”
mentioning
confidence: 99%
“…When MP is held at −75 mV (by −95 pA) 50 µM ZD7288 does not alter evoked APs waveforms and rates in neuron 1 and related SEH in postsynaptic cells held at −80 mV (−220 pA). Interestingly, 'once cell2 had been depolarized at −60 mV, ZD7288 became effective and abolished the SEH' [18] . This is indeed an important result, but the MP of 2 nd cell is denoted to be −85 mV and also considerably less current was injected (−90 vs. −220 pA).…”
Section: Vta Da Neuronsmentioning
confidence: 99%
“…DA neurons of SNc have a depolarized RMP − resting membrane potential and in order to repolarize to −60 mV a negative current of ~65 pA is injected [18] . Upon the hyperpolarizing steps of −90 pA these neurons exhibit a sag (see Figure 4) with a maximal amplitude of ~20 mV during 1 s. No gap junction response was observed among the pairs of DA neurons, but there was either a train of APs or a single spike-evoked hyperpolarization (SEH) that was heterogeneous in terms of amplitudes.…”
Section: Vta Da Neuronsmentioning
confidence: 99%